C67A BLITZ-AF CANCER REGISTRY: BASELINE CHARACTERISTICS OF PATIENTS WITH ATRIAL FIBRILLATION AND CANCER. (18th May 2022) - Gulizia, Michele Massimo; Ameri, Pietro; Alings, Marco; Collins, Ronan; De Luca, Leonardo; Di Nisio, Marcello; Fabbri, Gianna; Gabrielli, Domenico; Janssens, Stefan; Maggioni, Aldo Pietro; Parrini, Iris; Pinto, Fausto J; et al.
Abstract: Background: Evidences on atrial fibrillation (AF) in patients with cancer are limited, specifically with respect to antithrombotic therapy. Methods: BLITZ-AF Cancer is a prospective, non-interventional study of the epidemiology and management of AF in patients with cancer. Patients were included from 112 cardiology units in Italy, Belgium, Netherlands, Spain, Portugal, and Ireland, based on the following criteria: age ≥18 years; documented cancer other than basal-cell or squamous-cell carcinoma of the skin diagnosed within 3 years; electrocardiographically confirmed AF within 1 year; no concomitant interventional study. Follow-up is ongoing. Results: From June 26 th, 2019 to Sep. 30 th, 2021, 1, 514 subjects were enrolled. The most frequent cancer locations were lung (14.9%), colorectal (14.1%), breast (13.9%), prostate (8.8%), and non-Hodgkin lymphoma (8.1%); 463 (30.6%) of participants had metastases. AF was first-detected in 323 (21.3%), paroxysmal in 460 (30.4%), persistent in 192 (12.7%), long-standing persistent in 33 (2.2%), and permanent in 506 (33.4%); 590 (39.0%) patients had symptoms attributable to AF. Baseline characteristics are presented in the Table . Males were more than women and almost half of the subjects was >75 years-old. Cardiovascular risk factors were common and approximately 31% had heart failure or coronary artery disease. Previous thromboembolic and haemorrhagic events had occurred in 14% and 10% of subjects, respectively. The median CHA2 DS2 VASc score was 3. As shown in the Figure, the prescription of oral anticoagulants, especially direct-acting ones (DOACs), rose after the cardiology assessment, while the percentage of participants without any antithrombotic therapy declined. Among 1, 427 patients with non-valvular AF (i.e., no mitral stenosis or prosthetic mechanical valve), 997 (69.9%) were prescribed on DOACs at discharge/after consultation. At multivariable logistic regression analysis, variables associated with DOAC use were female sex (OR 1.58, 95% CI 1.22-2.05), age (OR 2.00, 95% CI 1.39-2.88 and OR 2.63, 95%CI 1.84-3.76, respectively, for 65-74 years and ≥75 years vs <65 years), hypertension (OR 1.43, 95%CI 1.10-1.87), long-standing persistent or permanent AF (OR 1.36, 95%CI 1.05-1.78). Haemoglobin <12 g/dL (OR 0.57, 95%CI 0.45-0.73), and planned cancer treatment (OR 0.72, 95%CI 0.57-0.92) were independently associated with a lower prescription of DOACs. Conclusions: BLITZ-AF Cancer provides extensive information on a large, contemporary cohort of individuals with AF and cancer. This baseline snapshot indicates that cardiologists pursue the implementation of DOACs in these patients, although residual use of other antithrombotic therapies or lack of any thrombo-prophylaxis remains substantial.